2020
DOI: 10.1177/1369433220939210
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening of steel decks for cable-stayed bridge using ultra-high performance concrete: A case study

Abstract: Fatigue cracking induced by vehicle load is a prevalent problem in orthotropic steel decks. In addition, pavement debonding in steel bridge decks is another familiar issue resulting from low slip resistance in the faying surface between the steel and asphalt concrete. The present study proposed a strengthening method that uses ultra-high performance concrete to stiffen a repeatedly maintained cable-stayed bridge in order to help address these two problems. The existing issues of the real bridge and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Once debonding occurs, the cracks multiply and enlarge, and spread towards the top compression fibre of the beams until failure, as can be seen in Figure 10. Many studies reported that debonding is a major problem faced by strengthening systems using UHPC (Prem et al , 2015; Zhang et al , 2020; Wang et al , 2020; Milovancevic et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Once debonding occurs, the cracks multiply and enlarge, and spread towards the top compression fibre of the beams until failure, as can be seen in Figure 10. Many studies reported that debonding is a major problem faced by strengthening systems using UHPC (Prem et al , 2015; Zhang et al , 2020; Wang et al , 2020; Milovancevic et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, a composite structure composed by the original OSD and UHPC is compactly formed through densely distributed shear nails. The steel-UHPC composite structure is not only used in new construction projects (Zhang et al, 2016), but also has been widely used in reinforcement projects, such as Yangtze River Bridge in China (Qin et al, 2022), Tianjin Haihe Bridge in China (Wang et al, 2020). After the strengthening of UHPC, an improvement of the fatigue resistance of the OSD can be expected.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to its exceptional strength, toughness, and durability (Shi et al, 2015), ultra-high-performance concrete (UHPC) has been used to reinforce the local stiffness of the OSDs under concentrated wheel loads, without significantly increasing the self-weight (Dieng et al, 2013;Shao et al, 2013). Initially, UHPC was utilized as a substitute for asphalt to resurface damaged OSDs (Zhu et al, 2018;Wang et al, 2020Wang et al, , 2021. Later, in some newly constructed bridges in China, the UHPC layer was cast monolithically after completing steel girder construction (Xue et al, 2020).…”
Section: Introductionmentioning
confidence: 99%